(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The Mesozoic Portuguese geological heritage is very rich and varied, a legacy of the position in the western margin of Iberia and its relationship with the evolution of the North Atlantic, with an interesting tectonic history since the Late Triassic. Regarding the Upper Jurassic several connections can be established between the tectonics and the stratigraphic record in the area surrounding the Caldas da Rainha structure: the basement and salt pillow control on deposition; the beginning of a diapiric and magmatic cycle associated to the on-set of sea-floor and the exhumation of both Jurassic deposits and the core of their controlling diapirs. The nature of the outcrops and richness in sedimentary environments, related with the different phases of rifting, is a remarkable case for extensional basin studies. Geological sites can be of regional, national or international importance due to scientific, educational, economical, social or historical reasons. The present proposal can be considered as a model for the establishment of tourist/educational routes with a strong component in communication on Earth Sciences, integrating social and historical aspects at a regional level. The recognition of those sites as geoheritage may contribute to a more sustainable management, in particular because it allows the achievement of a critical dimension for the investment in human resources and marketing. In Portugal, recent legal evolution might be considered promising. Nevertheless, since implementation of the concept of protected site depends on the approval of detailed management programs, there are frequent delays, misinterpretations and disrespect of legislation. The strategy to be adopted must integrate conservation, scientific studies and science communication in projects with economic and social interest.